Comparison of systemic treatments for previously treated patients with unresectable colorectal liver metastases: a systematic review and network meta-analysis - Jiang, Yunlin; Zhao, Mingye; Tang, Wenxi; Zheng, Xueping (Frontiers in Oncology, 2024)
Background There is limited evidence of comparative results among different treatments for patients with unresectable colorectal liver metastases (CRLM) who have failed at least one line of previous systemic therapy. We aimed to compare the efficacy of systemic treatments among these patients through this investigation. Methods We collected randomized controlled trials (RCTs) reported in English up until July 2023, from databases including PubMed, Embase, Cochrane Library, ClinicalTrials.gov, and prominent conference databases, for this Bayesian network meta-analysis. Phase II or III trials that evaluated at least two therapeutic regimens were included. Primary outcome was overall survival (OS), secondary outcome was progression-free survival (PFS). Hazards ratios (HRs) with 95% confidence intervals (CIs) were used as effect size. Subgroup analysis was performed based on metastatic sites. The current systematic review protocol was registered on PROSPERO (CRD42023420498). Results 30 RCTs were included, with a total of 13,511 patients. Compared to chemotherapy, multi-targeted therapy (HR 0.57, 95% CI 0.37–0.87) and targeted therapy plus chemotherapy (HR 0.78, 95% CI 0.67–0.91) show significant advantages. Targeted therapy (HR 0.92, 95% CI 0.54–1.57) and local treatment plus chemotherapy (HR 1.03, 95% CI 0.85–1.23) had comparable performance. For patients with liver metastases, TAS-102 plus bevacizumab, aflibercept plus fluorouracil-based combination chemotherapy (CTFU), and bevacizumab plus capecitabine-based combination chemotherapy (CTCA) showed the best outcomes in terms of OS. Bevacizumab plus intensified CTFU, bevacizumab plus CTCA, and HAI followed by single-agent chemotherapy (SingleCT) performed the best regarding PFS. For patients with liver-limited metastases, aflibercept plus CTFU is the optimal choice in OS. For PFS, the best options were HAI followed by SingleCT, aflibercept plus CTFU, and panitumumab plus CTFU. For patients with multiple-site metastases, the best treatments were TAS-102 plus bevacizumab, bevacizumab plus CTCA, bevacizumab plus CTFU, and aflibercept plus CTFU. Conclusion Multi-targeted therapy and targeted therapy plus chemotherapy are the best treatment mechanisms. TAS-102 plus bevacizumab is superior in OS, the combination of anti-VEGF drugs like bevacizumab and aflibercept with standard chemotherapy is the preferred option for CRLM patients.